Attitude towards birth control of married and unmarried people of Chittagong (Chittagong University Journal of Biological Sciences, 2013)
The study was designed to investigate the attitude towards birth control of the married & unmarried people using the Bengali version of the Wang and Thurstone, 1930 scale. The objective of the study was to see whether married and unmarried people differ in their attitude towards birth control. The sample consisted of 120 adults divided into 2 groups on the basis of marital status. Sixty married people (30 married males and 30 married females) and 60 unmarried people (30 unmarried males and 30 unmarried females) were the respondents of this study. The two groups of samples were selected at random. The result showed that the difference of attitude towards birth control of the married & unmarried people is not significant. Both groups possess favorable attitude towards birth control. DOI: http://dx.doi.org/10.3329/cujbs.v6i1-2.17087 The Chittagong Univ. J. B. Sci.,Vol. 6(1&2):97-106, 2011